Genome wide association studies and candidate gene mining for understanding the genetic basis of straw silica content in a set of Oryza nivara (Sharma et Shastry) accessions - Gowda, Rakshith S. R.; Sharma, Sandeep; Gill, Ranvir Singh; Mangat, Gurjit Singh; Bhatia, Dharminder (Frontiers in Plant Science, 2023)
Rice is a high-silica (SiO2·nH2O) accumulator. Silicon (Si) is designated as a beneficial element associated with multiple positive effects on crops. However, the presence of high silica content is detrimental to rice straw management, hampering its use as animal feed and as raw material in multiple industries. Rice straw management is a serious concern in north-western India, and it is eventually burned in situ by farmers, contributing to air pollution. A practical solution could lie in reducing the silica content in rice while also attaining sound plant growth. A set of 258 Oryza nivara accessions along with 25 cultivated varieties of Oryza sativa was used to assess the variation in straw silica content using the molybdenum blue colorimetry method. A large continuous variation was observed for straw silica content in O. nivara accessions, ranging from 5.08% to 16%, while it varied from 6.18% to 15.81% in the cultivated varieties. The O. nivara accessions containing 43%–54% lower straw silica content than the currently prominent cultivated varieties in the region were identified. A set of 22,528 high-quality single nucleotide polymorphisms (SNPs) among 258 O. nivara accessions was used for estimating population structure and genome-wide association studies (GWAS). A weak population structure with 59% admixtures was identified among O. nivara accessions. Further, multi-locus GWAS revealed the presence of 14 marker-trait associations (MTAs) for straw silica content, with six of them co-localizing with previously reported quantitative trait loci (QTL). Twelve out of 14 MTAs showed statistically significant allelic differences. Thorough candidate gene analyses revealed the presence of promising candidate genes, including those encoding the ATP-binding cassette (ABC) transporter, Casparian thickening, multi-drug and toxin extrusion (MATE) protein, F-box, and MYB-transcription factors. Besides, ortho-QTLs among rice and maize genomes were identified, which could open ways for further genetic analysis of this trait. The findings of the study could aid in further understanding and characterizing genes for Si transport and regulation in the plant body. The donors carrying the alleles for lower straw silica content can be used in further marker-assisted breeding programs to develop rice varieties with lower silica content and higher yield potential.